PROFILING KONDISI FISIK ATLIT WUSHU SURABAYA - Muhammad Wahyono; Ramadhany Hananto Puriana; Ismawandi Bripandika; Bayu Akbar Harmono; Angga Indra Kusuma; Eka Kurnia Darisman; Gatot Margisal Utomo; Mulyono; Yandika Fefrian Rosmi; Moh. Hanafi (Universitas PGRI Adi Buana Surabaya, 2023)
In the context of preparation for the Wushu Puslatkot Surabaya Athletes program, it requires a lot of references on how to maximize the training program. Therefore, it is necessary to hold physical tests for athletes aimed at making a physical training program. The implementation of the Community Service Program activities by the Physical Education Lecturer Team at PGRI Adi Buana University, Surabaya, went smoothly. The Wushu Trainers and Athletes are very enthusiastic about participating in every activity that has been scheduled. In the context of preparing Porprov, it is necessary to carry out an analysis and evaluation related to the physical training program and references on how to prepare the physical conditions and techniques used. Starting from the knowledge of how to train physically and techniques in achieving the targets set by the coach